A case report of nonhealing leg ulcer infected with Stenotrophomonas maltophilia in an immunocompetent patient in a Tertiary Care Hospital of Eastern India - Kalidas Rit; Rajdeep Saha; Parthasarathi Chakrabarty; Bipasa Chakraborty (Wolters Kluwer Medknow Publications, 2015)
Stenotrophomonas maltophilia is an aerobic, motile Gram-negative, nonfermentative bacillus considered as an opportunistic pathogen causing infection typically in individuals with immunosuppression, organ transplantation and malignancies. Contaminated water or medical devices in the hospital environment are the primary causes of infection. Here, we report a case of nonhealing leg ulcer infected with S. maltophilia in an immunocompetent individual.